Synthesis of N,N-Disubstituted 3-Oxo-2-phenyl-2,3-dihydro-1,2,4-thiadiazoles: Oxidative debenzylation and cyclization of 1,1,5-trisubstituted S-benzyl-2-thioisobiurets - Pandey A.K.; Singh R.; Verma V.K. (My University, 2025)
[No abstract available]